2020
DOI: 10.1093/sleep/zsaa064
|View full text |Cite
|
Sign up to set email alerts
|

Increased oscillatory frequency of sleep spindles in combat-exposed veteran men with post-traumatic stress disorder

Abstract: Study Objectives Sleep disturbances are core symptoms of post-traumatic stress disorder (PTSD), but reliable sleep markers of PTSD have yet to be identified. Sleep spindles are important brain waves associated with sleep protection and sleep-dependent memory consolidation. The present study tested whether sleep spindles are altered in individuals with PTSD and whether the findings are reproducible across nights and subsamples of the study. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…The sample used in the present study was the same as that used in our previous work, in which we reported the clinical characteristics and sleep architecture parameters of the participants ( Laxminarayan et al, 2020 , Wang et al, 2020a , Wang et al, 2020b ). Briefly, PTSD and non-PTSD participants did not differ significantly with respect to age or the Apnea-Hypopnea Index (AHI) in both the discovery and replication sets ( p > 0.05).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample used in the present study was the same as that used in our previous work, in which we reported the clinical characteristics and sleep architecture parameters of the participants ( Laxminarayan et al, 2020 , Wang et al, 2020a , Wang et al, 2020b ). Briefly, PTSD and non-PTSD participants did not differ significantly with respect to age or the Apnea-Hypopnea Index (AHI) in both the discovery and replication sets ( p > 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…We visually scored sleep stages in 30-s epochs for each night according to the American Academy of Sleep Medicine standards. The EEG preprocessing and spindle detection methods were as previously described ( Wang et al, 2020b ). Briefly, we segmented the data into 5-s epochs and used previously validated algorithms ( Brunner et al, 1996 , Doman et al, 1995 , Liu et al, 2018 ) to remove all epochs contaminated by muscle and ocular artifacts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, sleep is more fragmented with more nocturnal awakenings and increased arousal [1,2,66]. With regard to the sleep architecture in PTSD, the results are not consistent, with some studies finding an increase in the proportion of REM sleep and others finding a decrease [3,4,67]. Examples of these findings are shown in Figure 1.…”
Section: Sleep Characteristics In Military Ptsdmentioning
confidence: 99%